REDESAIN RUANG RAMAH ANAK PADA TEMPAT PENITIPAN ANAK GRIYA ANAK SURABAYA - Melania Rahadiyanti; Dyah Kusuma Wardhani; Etha Rambung; Hanna Tabitha Hasianna Silitonga (Institut Teknologi Dirgantara Adisutjipto, 2021)
Daycare play an important role in the growth and development of children who are active in it, because its main function is as a place to play and learn for children. It is important that daycare are designed according to the need for child-friendly spaces to create conditions that are comfortable and safe for children. This community service would like to be involved in creating a child-friendly space in one of the daycare, Griya Anak in Surabaya. This activity is carried out in several stages, namely preparation in the form of field observations, planning, namely designing the space used as the main activity in Griya Anak, counseling about child-friendly spaces and discussion of design results, then implementing rearranging and providing furniture needed to support the activities in Griya Anak. The results of this activity include the creation of a main activity space design at Griya Anak that is more comfortable and safer for children, and effective for the flow of activities carried out by the Griya Anak management, as well as the fulfillment of the need for appropriate furniture to support activities at Griya Anak.